Exploring food acceptance of army recruits during basic recruit training (BT) with focus groups - Nurhazwani Abdullah; Nurul Aziah Ahmad; Aikal Liyani Mohd Rasdi (2014)
Impact of basic recruit training (BT) on food acceptance was extensively studied but there were limited possible strategies to improve the food acceptance in order to minimize the potential losses of nutritional status during BT especially in the Malaysian Armed Forces.Thus, this research was conducted to study the food acceptance of army recruits for the purpose of menu planning during BT training. 68 male army recruits were selected as study respondents with purposive sampling. They were given consent form and a thorough study description was explained to the respondents. Focus group discussion was used for data gathering. A set of questions used for focus groups are modified from (Skiller, Booth, Coad, & Forbes-ewan, 2005) for question validity. Questions were asked to stimulate comments and to explain why they consumed certain items of food and reject some other food. The army recruits participating in the study were asked to sit at a particular table in the dining hall to be audio taped on 7 sessions. Each session of focus groups comprised of 8 to 10 individuals and the session lasted about 1 hour. One moderator and one observer conducted the interviews, transcribed and analysed. For the purpose of reliability, reliability intercoder was calculated between the two coders. Result of the intercoder analysis was Kappa=0.652 (p<0.05) which showed a good agreement (in range of 0.60 to 0.80) of reliability intercoder according to Practical Statistics for Medical Research (Altman, 1991). Thematic analysis was used to understand why they like or reject the foods from the focus group discussion and analyse with Atlas Ti. Food acceptance evaluated showed that during BT, the recruits choose to eat the food because to save budget, good taste and extra portion. Whereas, they avoid certain food due to less authentic, too oily, and hard food texture. The recruits demand for supper and frequent snack time and emphasized on extra food during vigorous training Their perception on the military meals are acceptable with medium quality but needs improvement, especially the taste. They suggested to add more menu like hometown local cuisines to increase the food acceptance ratings. The military meals served during basic recruit training are minimally acceptable but still needs improvement in terms of taste. Hence, planning the menu with more acceptable meals is recommended. This is important to maximize the food intake so that the body weight and composition is maintained during basic recruit training.